Pengaruh Kecepatan Aliran Terhadap Gerusan Lokal Pada Pilar Jembatan Berbentuk Lingkaran, Persegi Dan Jajaran Genjang - Syafitri, Yoga Dwi Fira; Rizal, Nanang Saiful; Kuryanto, Totok Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
Research on the effect of flow velocity on local scour on bridge pillars was analyzed using 2 methods, namely physical analysis and analysis using empirical methods. Physical analysis was carried out by direct measurements in the laboratory using bridge pillar prototypes. Analysis using empirical methods was carried out to determine the suitability of the formula used in calculating local scour to the results of physical analysis. The shapes of the pillars to be tested are square, circle and parallelogram with a width of 5 cm and a height of 15 cm. The discharge used in this research has 4 discharge variations. Based on the results of the physical analysis, it was found that the maximum scour depth at discharge was 404605.263 cm3/sec which occurred at square pillars = 2.5 cm, circles = 2.0 cm and parallelograms = 2.5 cm. The analysis uses empirical methods which have scour depths: Laursen and Toch method = 5.791 cm, Wu method = 1.87 cm and Froehclich method = 2.957 cm. Of the three methods, the Froehlich method has results that are closer to laboratory results. Of the 2 analysis methods, circular pillars are the best choice to use because circular pillars do not make an angle to the flow direction so they have the smallest scour value at each discharge.